Scleroderma From Pathogenesis to Comprehensive Management - Varga, John.; Denton, Christopher P.; Wigley, Fredrick M.; Allanore, Yannick; Kuwana, Masataka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Comprised of the authoritative work of international experts, this fully-updated second edition of Scleroderma builds upon the well-regarded approach in the first edition to provide integrated, concise, and up-to-date synthesis of current concepts of pathogenesis and modern approaches to management of systemic sclerosis (scleroderma). With a multidisciplinary approach to comprehensive care, this book is easily accessible for health care professionals in many fields. The new edition includes extensive updated material based on major developments in the field, with new chapters on personalized medicine, cancer complications, global perspectives on scleroderma, and more. It presents a succinct and thoughtful synthesis of current pathomechanistic concepts, providing a valuable reference tool for basic and translational investigators working in the field. Scleroderma: From Pathogenesis to Comprehensive Management serves as an essential, all-inclusive resource for rheumatologists, pulmonologists, cardiologists, gastroenterologists, nephrologists and all those involved in the care of scleroderma patients.
Section I. Introduction -- Historical Perspective of Scleroderma -- Section II. Epidemiology, Genetics and Classification -- Epidemiology, Environmental and Infectious Risk Factors -- Genetic Factors -- Disease Subsets in Clinical Practice -- Evolving Concepts of Diagnosis and Classification -- Overlap Syndromes -- Juvenile Localized and Systemic Scleroderma -- Morphea (Localized Scleroderma) -- Scleroderma Mimics -- Systems Biology Approaches to Understanding the Pathogenesis of Systemic Sclerosis -- Section III: The Biological Basis of Systemic Sclerosis -- Introduction: The Etiopathogenesis of Systemic Sclerosis: An Integrated Overview -- Pathology of Systemic Sclerosis -- Inflammation and Immunity -- Autoantibodies as Markers and Possible Mediators of Scleroderma Pathogenesis -- The Clinical Aspects of Autoantibodies -- Mechanisms of Vascular Disease -- Biomarkers in Systemic Sclerosis -- Pathophysiology of Fibrosis in Systemic Sclerosis -- Overview of Animal Models -- Section IV. Cardiovascular Manifestations and Management -- Raynaud$1 (Bs Phenomenon, Digital Ulcers, and Nailfold Capillaroscopy -- Renal Crisis and Other Renal Manifestations of Scleroderma -- Cardiac Involvement -- Section V. Pulmonary Manifestations and Management -- Overview of Lung Involvement: Diagnosis, Differential Diagnosis, and Monitoring -- Clinical Assessment of Lung Disease -- Treatment of Interstitial Lung Disease -- Pathogenesis of Pulmonary Arterial Hypertension -- Clinical Assessment of Pulmonary Hypertension -- The Management of Pulmonary Arterial Hypertension in the Setting of Systemic Sclerosis -- Section VI. Gastrointestinal Manifestations and Management -- Overview of Gastrointestinal Tract Involvement -- Upper Gastrointestinal Tract: Manifestations of Systemic Sclerosis -- Small and Large Intestinal Involvement and Nutritional Issues -- Section VII. Skin, Musculoskeletal and Other Complications -- Calcinosis -- Evaluation and Management of Skin Disease -- Assessment and Management of Progressive Skin Involvement in Diffuse Scleroderma -- Skeletal Muscle Involvement -- Tendons, Joints, and Bone -- Cancer in Systemic Sclerosis -- Overlooked Manifestations -- Pregnancy -- Section VIII: Management and Outcome Assessment -- Introduction to Section VIII: Management and Outcome Assessment -- Immunomodulatory, Immunoablative, and Biologic Therapies -- Investigative Approaches to Drug Therapy -- Drug Development and Regulatory Considerations for SSc Therapies -- Physical and Occupational Therapy -- Psychosocial Issues and Care for Patients with Systemic Sclerosis -- Clinical Trial Design in Systemic Sclerosis -- Measuring Disease Activity and Outcomes in Clinical Trials -- Innovative Approaches to Clinical Trials in Systemic Sclerosis -- Molecular Stratification by Gene Expression as a Paradigm for Precision Medicine in Systemic Sclerosis -- Section IX. Case Studies: Approach to Complex Clinical Problems -- Managing the Ischemic Finger in Scleroderma -- Scleroderma Renal Crisis -- Rapid Diffuse Skin Disease with Progressive Joint Contractures -- Management of the Scleroderma Patient with Pulmonary Arterial Hypertension Failing Initial Therapy -- Pseudo-obstruction with Malabsorption and Malnutrition -- Progressive Interstitial Lung Disease Non-Response to Cyclophosphamide -- Coping with the Disfigurement of Scleroderma: Facial, Skin, and Hand Changes -- Managing Complicated Digital Ulcers .s
Keywords: Medicine; Dermatology; Respiratory organs -- Diseases; Rheumatology; Medicine & Public Health; Rheumatology; Pneumology/Respiratory System; Dermatology